مستوى التفكير التأملي لدى معلمات الرياضيات للصفوف الثلاثة الأولى في الأردن - الخزام، عوض مفلح شهاب (المركز القومي للبحوث بغزة, 2020)
هدفت هذه الدراسة التعرف إلى مستوى التفكير التأملي لدى معلمات الرياضيات للصفوف الثلاثة الأولى في ضوء متغيري الخبرة التعليمية والمؤهل العلمي، تكون مجتمع الدراسة من جميع معلمات الرياضيات للصفوف الثلاثة الأولى الذين في المدارس الحكومية في محافظة المفرق في الأردن خلال الفصل الدراسي الأول من العام الدراسي 2018/2019 والبالغ عددهن (835) معلمة، كما تكونت عينة الدراسة من (500) معلمة من معلمات الرياضيات للصفوف الثلاثة الأولى. اشتملت أداة الدراسة على استبانة مكونة من (30) فقرة لمقياس التفكير التأملي لأيزنك وولسون (Eysenck & Wilson, 1976)، المعرب والمطور، والذي قام بركات (2005) بتعريبه وتطويره وإعادة صياغته ليناسب البيئة العربية. استخدم الباحث المنهج الوصفي التحليلي بالصورة المسحية، وقد توصلت نتائج الدراسة إلى أن مستوى التفكير التأملي لدى معلمات الصفوف الثلاثة الأولى كان متوسطا على المقياس ككل حيث بلغ المتوسط الحسابي (1.35) وهي قيمة متوسطة، كما أظهرت النتائج وجود فروق دالة إحصائيا (0.05 ≥α) في مستوى التفكير التأملي لدى معلمات الرياضيات للصفوف الثلاثة الأولى تعزى للخبرة التدريسية ولصالح المعلمات ذوات الخبرة التدريسية (أكثر من 5 سنوات)، كما أظهرت النتائج أيضا وجود فروق دالة إحصائيا (0.05 ≥α) في مستوى التفكير التأملي لدى معلمات الرياضيات للضفوف الثلاثة الأولى تعزى للمؤهل العلمي ولصالح المعلمات ذوات المؤهل (أعلى من بكالوريوس).
The study was designed to identify the level of reflective thinking among mathematics teachers for the first three school classes in the light of the variables of educational experience and educational qualification., The study population of all the mathematics teachers for the first three grades in the public schools in the province of Mafraq in Jordan during the first semester of the academic year 2018/2019 and the number (835) teachers. The study sample consisted of (500) mathematics teachers for the first three school classes. The study included a questionnaire consisting of (30) paragraph of Eysenck and Wilson reflective thinking scale (Eysenck & Wilson, 1976), which Barakat (2005) Arabized and developed and reformulated to suit the Arab environment. The researcher used descriptive analytical method in the survey, the results of the study showed that the level of reflective thinking among mathematics teachers for the first three school classes was medium on the whole scale, where the mean was (1.35. The results also showed statistically significant differences (0.05≥α) In the level of reflective thinking of mathematics teachers for the first three grades due to the teaching experience and for the benefit of teachers with teaching experience (more than 5 years), The results also showed that there were statistically significant differences ( 0.05 ≥α ) in the level of reflective thinking among the mathematics teachers for the first three school classes due to the scientific qualification and to the benefit of teachers with qualification (higher than Bachelor.
Keywords: التفكير التأملي -- معلم الرياضيات -- الصفوف الثلاثة الأولى -- الأردن